Analysis of Drought and Flood Disasters During 0–1950 AD in the Hexi Corridor, China, Based on Historical Documents - Tang, Xia; Feng, Qi (Frontiers in Environmental Science, 2021)
It is important to analyze the characteristics of drought and flood change in an arid area over a long timescale for the evolution of the environment. Historical documents were used to reconstruct a drought and flood grade series for the Hexi Corridor from 0 to 1950 AD. The moving average and wavelet transform processing methods were used to determine the temporal evolution characteristics of droughts and floods, as well as the corresponding relationships with climate change and human activities in the Hexi Corridor after 1000 AD. The results showed the occurrence of eight drought phases (370–410 AD, 790–870 AD, 1050–1150 AD, 1260–1340 AD, 1430–1570 AD, 1710–1770 AD, 1800–1890 AD, and 1910–1950 AD), five flood phases (320–360 AD, 1670–710 AD, 1730–1790 AD, 1810–1860 AD, and 1880–1950 AD), and 3 oscillation periods of drought and flood events. Climate change may have been the main factor inducing droughts and floods before 1580 AD, whereas human activities may have increased the frequency of droughts and floods after the 16th century. Therefore, quantifying the impacts of natural factors and human activities on droughts and floods can provide important theoretical guidance for the prevention and reduction of future disasters.